Weight loss behaviour and its perceived barriers: Findings from in-depth interviews with overweight adolescents - Sidek, Suriati; Danis, Ajau; Md. Yusof b, Safiah (Nutrition Society of Malaysia, 2017)
Unhealthy weight loss behaviors among adolescents such as maladaptive eating to be thin and practicing dietary restrain has become a significant public health concern. These harmful ways in losing weight may cause disturbance in adolescent’s physical growth, cognitive development and social well-being. Therefore, this qualitative study aimed to explore the weight loss behavior among 33 overweight adolescent males (N = 15) and females (N = 18). Based on a thematic analysis on data from in-depth interviews, the present study found that adolescents engaged in various types of weight loss behaviour and these include attempts at dieting, engaging in physical activity and consuming slimming products. Even though overweight adolescents believe that a combination of balanced diet and exercise are the pivotal keys to effective weight reduction and lead to a healthy lifestyle, they were more likely to involve in dieting compared to any other approaches, particularly engaging in skipping meals. However, their preferences of weight loss behaviour are influenced by sources of information obtained from the family members and the media, parents modelling in eating pattern, and are limited by some of the barriers that include laziness, desire for foods and inconvenience to exercise. Weight reduction intervention targeting overweight adolescents is therefore urgently required.